Poverty Dynamics among Kenyan Refugees During COVID-19: A Heteroscedasticity Consistent Ordered Probit Model - Oyekale, Abayomi (Acta Universitatis Danubius. Œconomica, 2022)
COVID-19 remains an income shock of significant economic consequence to many households across the world. The situation among refugees can be pathetic due to their inherent economic deprivations and vulnerability to income shocks. This paper analyzed the dynamics of poverty among refugees in Kenya during the COVID-19 pandemic and determined their correlates. The data were the first five waves of the were the COVID-19 Rapid Response Phone Surveys that were conducted among refugees. The data were analysed with heteroscedasticity consistent Ordered Probit model. The results showed that with only 8.14% never entering poverty within the survey periods, majority of the refugees were transiently (46.27%) and chronically (45.59%) poor. The error variance differed across household sizes, and heteroscedasticity properly corrected. Movement from never being poor to chronic poverty was significantly promoted by urban residence, household size, educational levels, and camp of residence (Kakuma, Dadaab and Kalobeyei), while asset disposal income, amount of credit, remittance, and other gifts reduced it. It was concluded that efforts to reduce poverty vulnerability among refugees should among others address maternal fertility and promotion of policies to allow formally educated refugees to be gainfully engaged in the Kenyan labour markets.